(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Reliable wireless communication is a critical enabler of digital transformation in the mining industry, particularly in phosphate and mineral extraction environments, where safety, monitoring, and automation depend on robust connectivity. However, underground and semi-enclosed mining settings introduce severe electromagnetic (EM) challenges, including signal attenuation, multipath fading, and interference from dense equipment and layered geological structures. Traditional substrate engineering methods—such as buried diffused layers (BDL), metallized grids, guard rings, and electromagnetic bandgap (EBG) structures—offer partial isolation but often fail to ensure stable performance in such harsh conditions. This paper proposes the application of a game-theoretic electromagnetic isolation framework to wireless communication systems in mining operations. By modeling isolation techniques as strategic players in a non-cooperative game, the framework derives equilibrium solutions that balance isolation, insertion loss, fabrication complexity, and deployment cost. Simulation studies across the 2–12 GHz band demonstrate that the proposed method achieves 25–30 dB improvements in coupling reduction compared to conventional approaches while maintaining practical scalability. These results highlight the potential of the framework to enable safe, interference-resilient, and efficient wireless connectivity for real-time monitoring, autonomous equipment control, and worker safety systems in phosphate and mineral mining environments.